Dietary habits, nutritional knowledge, and nutritional status among cardiological patients, including those with obesity and diabetes - Sapała, Anna-Maria; Staśkiewicz-Bartecka, Wiktoria; Grochowska-Niedworok, Elżbieta; Kardas, Marek (Frontiers in Nutrition, 2024)
Background: Cardiovascular disease is a leading cause of death worldwide. The increase in patients with obesity and diabetes raises the risk of cardiovascular diseases. Proper eating habits and adequate nutritional knowledge play a key role in preventing and treating these conditions. This study aimed to evaluate the dietary habits, nutritional knowledge, and nutritional status of patients hospitalized in a cardiology department in Poland, including those with obesity or diabetes. Methods: The study was conducted at St. Barbara Regional Specialized Hospital No. 5 in Sosnowiec from January to June 2021, involving 301 patients, 154 women (51.2%) and 147 men (48.8%), aged 29 to 87. Participants were assessed for BMI, NRS 2002 scale, morphology, biochemistry results, blood pressure, and examined for nutritional knowledge and habits using proprietary questionnaires. A proprietary scale was used to assess eating habits. Results: Most cardiology patients were overweight or obese, with 80% exceeding the normal weight range. No significant gender differences were noted in malnutrition risk on the NRS 2002 scale. The study found patients rarely consumed recommended amounts of vegetables, fruits, legumes, whole grains, fish, and dairy products. Only 26.2% regularly ate a second breakfast, and just 9.3% chose water with meals. However, consumption of salty snacks, energy drinks, and alcohol was low. Biochemical and blood test analysis did not show significant differences between patients with diabetes, obesity, and others. Conclusions: Most cardiology patients were overweight or obese, which poses a significant risk for further health complications, including cardiovascular diseases. Although patients with diabetes and/or obesity had better nutritional knowledge in some areas, this did not lead to healthier eating habits. The absence of significant differences in biochemical tests suggests that overall lifestyle and diet are crucial to cardiovascular health.